Barriers to Exclusive Breastfeeding for Mothers in Tswelopele Municipality, Free State Province, South Africa: A Qualitative Study - Simthandile Rebecca Quebu; Daphne Murray; Uchenna Benedine Okafor (MDPI AG, 2023)
Despite the numerous advantages of exclusive breastfeeding (EBF), the practice remains infrequently adopted in certain countries and is also associated with context-specific obstacles. Consequently, this study explores the experiences and opinions of mothers about the barriers and support systems of exclusive breastfeeding (EBF), in a bid to promote this practice in the Tswelopele Municipality of the Free State Province of South Africa. In-depth individual, semi-structured interviews were conducted with 16 mothers, using an audio recorder after receiving their permission to record the interviews. The analysis of the collected data revealed that opinions clustered around four topics: mother-related barriers to EBF, baby-related barriers to EBF, support systems to enhance EBF, and complications caused by barriers to EBF. The findings from these themes and sub-themes imply that the maternal factor is strongly influenced by other factors regarding the success or failure of this practice. These include extreme breast discomfort, maternal illness, the fear that the mother's milk supply is insufficient, a lack of understanding about EBF, and the influence of different cultural factors. When mothers encounter difficulties with breastfeeding, these challenges may impede their ability to practice EBF. In addition, while some participants were eager to breastfeed their babies and continued EBF for a period of six months, their infant's health and behavioral issues prevented them from doing so. Some of these problems included infant sickness and crying. From the prenatal to the postnatal period, mothers and their families should have access to breastfeeding education and counseling, along with sufficient time to make informed infant nutrition decisions. During counseling sessions, conversations with these stakeholders should focus on fostering a realistic understanding regarding what to expect when breastfeeding for the very first time, debunking breastfeeding-related misconceptions, and addressing inaccurate information and concerns. In addition, health professionals must be empathic and respectful of the mother's traditions and cultures and must also educate mothers and their families on the importance of EBF. Our list of themes and sub-themes could be utilized to enlighten exclusive breastfeeding challenges and potential mitigation efforts, not only in Tswelopele Municipality, South Africa but also in a number of other geographical contexts.